2015
DOI: 10.1186/s12916-015-0338-z
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Consumption of whole grains and cereal fiber and total and cause-specific mortality: prospective analysis of 367,442 individuals

Abstract: This is an Erratum to BMC Medicine 2015, 13:59, highlighting previously undeclared competing interests and including more information in the acknowledgements section.Please see related article: http://www.biomedcentral.com/1741-7015/13/59

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A meta-analysis done by Huang et al [87] showed that a high consumption of whole grains or cereal fibre could be related to a reduced risk of NCDs.…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…A meta-analysis done by Huang et al [87] showed that a high consumption of whole grains or cereal fibre could be related to a reduced risk of NCDs.…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…Previous studies have shown that grains such as corn, oats, and wheat contribute only 1.1% of total calories in the average diet. However, the higher cost, longer cooking times, and less appealing appearance of whole grains may deter some consumers from incorporating them into their diets [ 39 , 40 ]. As a country with a high burden of ischemic stroke, China could potentially reduce its stroke risk by encouraging its population to switch from polished rice to whole grain rice.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, several meta-analyses have displayed that a higher dietary fiber intake is linked with a lower relative risk of total all-cause mortality among 16-23% [156][157][158]. On the other hand, several clinical trials have studied the link between diet and inflammation, and more specifically, the impact of dietary fiber.…”
Section: Fibermentioning
confidence: 99%